2016
DOI: 10.4014/jmb.1603.03078
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Population in Intestines of Litopenaeus vannamei Fed Different Probiotics or Probiotic Supernatant

Abstract: The interactions of microbiota in the gut play an important role in promoting or maintaining the health of hosts. In this study, in order to investigate and compare the effects of dietary supplementation with HC-2 (HC-2), NRW-2, or the bacteria-free supernatant of a HC-2 culture on the bacterial composition of , Illumina sequencing of the V1-V2 region of the 16S rRNA gene was used. The results showed that unique species exclusively existed in specific dietary groups, and the abundance of Actinobacteria was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 37 publications
13
35
0
3
Order By: Relevance
“…The promotion of changes in the composition of the intestinal microbiota is a key component of the case for using MOS as prebiotics, but this aspect has also been one of the least developed. The composition of the microbiota of shrimp under control conditions is consistent with previous research on this species, agreeing that Proteobacteria is the dominant phylum, with relative abundance levels between 28 and 70% [44][45][46][47][48][53][54][55][56][57] . Other phyla showing high abundance under control conditions were Bacteroidetes (22%) and Actinobacteria (11%), whose values matched those in some of the previous studies; however, overall, those studies showed variable relative abundance levels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The promotion of changes in the composition of the intestinal microbiota is a key component of the case for using MOS as prebiotics, but this aspect has also been one of the least developed. The composition of the microbiota of shrimp under control conditions is consistent with previous research on this species, agreeing that Proteobacteria is the dominant phylum, with relative abundance levels between 28 and 70% [44][45][46][47][48][53][54][55][56][57] . Other phyla showing high abundance under control conditions were Bacteroidetes (22%) and Actinobacteria (11%), whose values matched those in some of the previous studies; however, overall, those studies showed variable relative abundance levels.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of the inclusion of MOS on the microbiota of shrimp is reflected in the relative abundance at the phylum level, with the predominance of Actinobacteria over Proteobacteria and without any previous background about the displacement of the phylum Proteobacteria by the phylum Actinobacteria in association with a dietary intervention in this species. However, using NGS, it has been reported for L. vannamei that dietary supplementation with the supernatant from the bacterial strain HC-2 46 or with cornstarch as a source of carbohydrates 45 leads to changes associated with increases in Actinobacteria and Firmicutes, respectively, without affecting the position of Proteobacteria as the dominant phylum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the changes in the intestinal microvilli and the folding of the digestive epithelium varied between dietary groups, and obvious improvement in intestinal histology was observed after shrimp fed with the normal probiotic HC-2, and the intestinal tissue was not damaged after the shrimp were challenged by V. parahaemolyticus E1. These results are similar to the findings of Merrifield et al (2010) [33], who found that Pediococcus acidilactici - fed fish had significantly longer microvilli than other groups of fish, but are contrary to the findings of Sha et al (2016) [20], who reported that dietary HC-2 didn’t improve the intestinal morphology of L. vannamei . These differently phenomena may be attributable to the bacteria concentration used in the dietary is too low (10 7 CFU/g) than in this work (5×10 8 CFU/g), which hinder the HC-2 to be the dominant microflora in the shrimp intestines to improve the intestinal morphology.…”
Section: Discussionsupporting
confidence: 87%
“…The histology determine was carried out as described in Sha et al (2016) [20]. Five shrimps were freely selected from each treatment group upon termination of the feeding and challenge experiments and sampled the midguts to dissect and fix (60% absolute ethanol, 30% trichloromethane, 10% acetic acid) for 19 h. Following, the fixed tissues were dehydrated in ascending concentrations of alcohol (70, 80, 95, and 100%), cleared in toluene, embedded in paraffin, and sectioned at 10 μ m with a rotary microtome.…”
Section: Methodsmentioning
confidence: 99%